E-logistic Practices and Health Care Supply Chain Management for Public Referral Hospitals in Uganda - Kagoya, Sumaya M.; Mkwizu, Kezia H. (University of Dar es Salaam Library Journal, 2022)
This paper examined e-logistic practices and health care supply chain management in the context of Ugandan public referral hospitals. The prime objective was to examine the relationship between e-logistics operations and performance of health care supply chain management. A quantitative research approach was utilized to gather data from public referral hospitals respondents using structured survey questionnaires. For data analysis, descriptive statistics and Partial Least Squares-Structural Equation Modelling were utilised, aided by SmartPLS 3. Findings showed a positive significant relationship between e-logistics operations and performance of health care supply chain management in the context of Ugandan public referral hospitals. This study implies that the key e-logistics operations in relation to the performance of health care supply chain management, are central management of drugs, the correct order picking of drugs given to the right patients for quality control, and presence of an electronic system to update stock daily. Additionally, the findings designated that, e-logistics operations are related to the performance of health care supply chain management in terms of ICTs tracking systems and data transparency. The practical implication to the health sector- stakeholders, is to consider ICT-tracking systems and data transparency for e-logistics operations and performance of health care supply chain management.